The Effect of Glycosylated Soy Protein Isolate on the Stability of Lutein and Their Interaction Characteristics - Wang, Xia; Wang, Shaojia; Xu, Duoxia; Peng, Jingwei; Gao, Wei; Cao, Yanping (Frontiers in Nutrition, 2022)
Lutein is a natural fat-soluble carotenoid with a variety of physiological functions, but its poor water solubility and stability restrict its application in functional foods. In this study, glycosylated soy protein isolate (GSPI) was prepared using soy protein isolate (SPI) and inulin-type fructans (ITFs), and the stability and interaction mechanism of the complex of GSPI and Lutein were analyzed. The results showed that glycosylation reduced the fluorescence intensity and surface hydrophobicity of SPI, while the emulsification and solubility were improved. Fluorescence intensity and UV-Vis results showed that Lutein and GSPI formed a complex, and Lutein quenched GSPI fluorescence statically. Combined with thermodynamic parameter analysis, it was found that Lutein and GSPI bound spontaneously through hydrophobic interaction, and the binding stoichiometry was 1: 1. The results of XRD analysis showed that Lutein and GSPI were combined in an amorphous form, and FTIR analysis found that Lutein had no effect on the secondary structure of GSPI. Simultaneously, the combination of Lutein and GSPI improved the water solubility of Lutein and the stability of light and heat.